Unconquered by the Blockade - E. M. Proshina (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the book of A.F. Izmailov, “Unconquered by the blockade”, the relevant topic is first considered through the history of human destinies, documentary memories of the participants in the events.